MIGRATION OF FIRST-YEAR STEPPE EAGLES (Aquila nipalensis) FROM NORTHERN KAZAKHSTAN AND IMPLICATIONS FOR CONSERVATION - Katzner, T.E.; Efrat, R.; Bragin, A.E.; Lehnardt, Y.; Bragin, E.A.; Sapir, N. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
Extensive anthropogenic alteration of steppe ecosystems throughout Eurasia leaves central Asia with some of the world’s last remaining large expanses of grassland habitat. Steppe eagles (Aquila nipalensis) are globally endangered breed primarily in these steppe ecosystems. We evaluated migratory movements of first year steppe eagles hatched in northern Kazakhstan, to understand their migration and the extent to which their movements expose them to threats that may impact population viability. Most steppe eagles we monitored migrated to the east of the Caspian Sea to wintering grounds on the Arabian Peninsula or northeastern Africa, although a few migrated to the west of the Caspian Sea, one wintered in southcentral Iran, and one in southern Pakistan. Northbound migration routes largely mirrored southbound routes. Straight-line distance between summering and wintering grounds averaged 3,582 km (fall) and 3,700 km (spring), and actual distance traveled averaged 7,183 km (fall) and 9,433 km (spring). Routes of travel of these steppe eagles expose them to potential electrocution, shooting, and wildlife trade across the extent of their migratory and wintering areas.
Миграция степного орла-первогодка (Aquila nipalensis) из Северного Казахстана и последствия для сохранения
Keywords: Aquila nipalensis; biotelemetry; bird migration; Middle East; shooting of birds; steppe ecosystems; wildlife trade